The effect of NPK compound fertilizer (27%:6%:10%) compared to conventional fertilizers on productive tea plants of GMB 7 clone in the Andisols soil type - Pudjo Rahardjo; Yati Rachmiati; Arkat Agus Salim (Research Institute for Tea and Cinchona, 2012)
The effectiveness application of compound fertilizer NPK (27%:6%:10%) to increase tea shoots had been tested in Experimental Garden of Research Institute for Tea and Cinchona Gambung, Bandung, West Java, from January 2006 to March 2007. Experimental design used was randomized block design with 6 treatments with five replication. The plot sizes were 20 x 20 m = 400 m2/plot. The tea clone tested was GMB 7. The application of compound fertilizer NPK (27%:6%:10%) were twice a year (50%-50%) and conventional fertlization were 4 times a year (20%-30%-20%-30%). The composition of treatment was as follows: (A) 500 kg, (B) 600 kg, (C) 700 kg, (D) 800 kg/ha/year, and (E) conventional fertilizer recommended dosage of the Research Institute for Tea and Cinchona Gambung (480 kg urea + 357 kg ZA + 260 kg SP 36 + 300 kg KCl + 278 kg kieserit/ha/year), and (F) control (no fertilizer treatment). Parameters observed were: 1. soil and leaf analysis at before and after treatment, 2. weighting the potential and the yield components each time of plucking, and 3. technoeconomic analysis. The results showed that: statistical analysis of the components as well as potential yield, and nutrient analysis (N, P, K, Mg and Zn) of the mother leaves of GMB 7 clones and the soil demonstrated the significantly differences among the treatments of all the various doses of compound fertilizer NPK and conventional fertilizer application to control (no fertilizer treatment). Meanwhile, there were no significantly differences among the result of the doses of compound fertilizer NPK, to the conventional fertilizer applications. Furthermore, dose of compound fertilizer NPK (27%:6%:10%) for productive tea plant was recommendated at 700 kg/ha rate and was equivalent to 189 kg N/ha/year or 63% of the dose of conventional fertilizer, but could provide equivalent result to conventional fertilizer application, and not only could save the buying cost of conventional fertilizer (urea, ZA, TSP/SP-36, KCl / MOP and kieserit) but also the cost of application cost in the field.